(untitled) (Heritage, 2025)
Although the deprivation of liberty is mentioned in the earliest legal sources from the year 1299, the study attempts to use narrative sources to determine whether the deprivation of liberty existed at all before 1299. The Life of St. Simeon by Stephen the First Crowned, written between 1208 and 1216, and Domentian’s Lives of St. Simeon and St. Sava, written in the 50s and 60s of the thirteenth century, are the two narrative sources used in this article. The terms caught, thrown (into a dungeon), dungeon, stone cave, shackles, taken and taken out are associated with deprivation of liberty in the work of Stephen the First Crowned, which demonstrates the prevalence of such deprivation in Raška in the 12th century. Domentian also uses other terms for deprivation of liberty, persecution, transgression, lawbreaker, introduced, thrown, shackled, prisoner (someone who is in prison - captive), sitting, eaves, guard and report in addition to the terms Stefan uses for shackles, chains, dungeon and stone cave. Since no incidents of deprivation of liberty are recorded in XIII, this indicates that the meaning of deprivation of liberty has increased in XIII and that the provisions in this regard are clarified in customary law.